Dos galpões dos bumbás de Parintins à aprendizagem de ciência: uma reflexão acerca do fazer artístico e suas implicações no contextos escolar - Silva, Suhellen Martins da (2016)
This study aimed to relate the diverse knowledges of the sociocultural approach seized in the sheds of Bumbás Parintins and its influence in the process of formal education and pedagogical practices. Given the complexity of the artistic and cultural space, the study was developed as outlined object that proposes to know: How line with the learning takes place in the demonstrations of different knowledges seized in sheds and these are related to science learning in the classroom? The textual structure is organized into four (04) chapters. The first one comes with a theoretical approach that discusses the concept of culture by entering the Parintins Folklore Festival and its characteristics, the relationship between culture, science, learning. The human craving for knowledge and how this knowledge was given throughout history. The second chapter is devoted to the methodological approach, it offers a general perception of the approach of methods, procedures and techniques employed during the survey and its participants: artists, students and teachers, essential in the investigation of this study process. The third chapter presents the construction of knowledge acquired in the sheds of Bumbás by leading artists¹ and conceptions as the relationship with formal education. And the fourth and final chapter, we highlight the perceptions of students and teachers about the influence of this cultural event in the school context.